Influence of CaO Addition, FeO/SiO2 , and MgO/SiO2 on the Melting Characteristic Temperatures of FeO-SiO2-MgO-CaO System - Yongbo Ma; Xueyan Du (Materials Research, 2019)
In order to decrease the oxidation temperature of fayalite in molten nickel slags, the influence of CaO addition, FeO/SiO2, and MgO/SiO2 on melting characteristic temperatures of FeO-SiO2-MgO-CaO system were investigated. The melting characteristic temperatures, including softening temperature (Ts), hemispherical temperature (Th), and flow temperature (Tf),were measured with hot stage microscope. Experimental results showed that the melting characteristic temperatures first decreased sharply and then increased slowly with increasing w(CaO) for samples at given FeO/SiO2 and MgO/SiO2 ratios. The melting characteristic temperatures of samples without CaO addition were much higher than that of samples with different CaO addition, which was mainly caused by the phase components at different compositions. The variation of melting characteristic temperatures were described in detail. Phase components and liquid fractions were calculated by FactSage 7.1, which was good agreement with the XRD patterns.